1994
DOI: 10.1177/00220345940730030501
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Hydroxyapatite-Ionomer Cements at 38°C

Abstract: This study describes the formation of a calcium polyacrylate-hydroxyapatite cement. Our hypothesis was that calcium phosphates would rapidly hydrolyze in the presence of polyacrylic acid (PAA) to form a cement. PAA, tetracalcium phosphate (TetCP), and dicalcium phosphate (DCP) were reacted together and formed calcium polyacrylate (CPA) and hydroxyapatite(HAp) within 10 h at 38 degrees C, resulting in hardened masses. Reaction times increased with decreasing (HApreactants)/PAA ratios. In the first of three reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…The first type is based on modification with (water-soluble) non-reactive polymers, such as hydroxypropylmethylcellulose [60] or chitosan [61]. In a second type of cements, the high reactivity and strong basic character of TTCP compared with other calcium phosphates is used to react with carboxylic acid or organic phosphate moieties of the polymer, such as polyacrylic acid [62][63][64], poly(methyl vinyl ether-maleic acid) [10,65], poly[bis(carboxylatophenoxy)phosphazene] [66], poly(vinyl phosphonate) [67][68][69] (Fig. 1).…”
Section: Polymeric Cementsmentioning
confidence: 99%
“…The first type is based on modification with (water-soluble) non-reactive polymers, such as hydroxypropylmethylcellulose [60] or chitosan [61]. In a second type of cements, the high reactivity and strong basic character of TTCP compared with other calcium phosphates is used to react with carboxylic acid or organic phosphate moieties of the polymer, such as polyacrylic acid [62][63][64], poly(methyl vinyl ether-maleic acid) [10,65], poly[bis(carboxylatophenoxy)phosphazene] [66], poly(vinyl phosphonate) [67][68][69] (Fig. 1).…”
Section: Polymeric Cementsmentioning
confidence: 99%
“…However, further investigations have shown that only the first nuclei consist of a nearly stoichiometric HA, whereas further growth of these nuclei occurs in the form of CDHA [145]. Besides, there is a study demonstrating that the initially formed stoichiometric HA further interacts with remaining DCPD to form CDHA [146].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, composites of ceramics with natural degrad-able polymers are attracted much interest as a bone filler. 16 -18 Several particle composites based on degradable biopolymers such as collagen, 19 fibrin glue, 20 starch-based material, 21 gelatin, 22,23 chitosan, 24,25 alginate, 26,27 and hydroxy-propyl-methyl cellulose 28 with inorganic powders, as bone filler were developed. 29 Recently, a mixture of HA powder (or HAP) and saline solution of sodium alginate was prepared by Maruyama et al 30 -32 This mixture was named HAP clay and showed excellent osteoconductive properties, bridging the gap between implants and cortical bone without any adverse reaction.…”
Section: Introductionmentioning
confidence: 99%